2023
DOI: 10.3389/fenrg.2023.1137941
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a multi-stage solar distiller associated with Fresnel lens in Malaysian weather

Abstract: Water scarcity is widely known as one of the major current issues. As of now, many solar distillers are using the same concept of evaporation and condensation of saline water to produce distillates. The main problem with such solar distillers is their low productivity, as the latent heat produced is lost to the surroundings. A multi-stage solar distiller can solve the issue of productivity by utilizing the latent heat released. This design consists of multiple solar distillers stacked one on top of the another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For both BSSS and TSSS, the application value depends on its fresh water yield performance. The methods to improve the fresh water yield of the BSSS and TSSS include adding a solar concentrator (Choong et al, 2020), designing a multi-stage still (Yeang et al, 2023), increasing the evaporation area by adding sand troughs (Nagaraju et al, 2022), adding the nanofluids (Sangeetha et al, 2022), and so on. In a study by Tiwar (Tiwar, 1988), it is concluded that the daily fresh water yield and the purity of the fresh water from a horizontal tubular solar seawater still (HTSSS) are higher than that from a BSSS under the same condition.…”
Section: Introductionmentioning
confidence: 99%
“…For both BSSS and TSSS, the application value depends on its fresh water yield performance. The methods to improve the fresh water yield of the BSSS and TSSS include adding a solar concentrator (Choong et al, 2020), designing a multi-stage still (Yeang et al, 2023), increasing the evaporation area by adding sand troughs (Nagaraju et al, 2022), adding the nanofluids (Sangeetha et al, 2022), and so on. In a study by Tiwar (Tiwar, 1988), it is concluded that the daily fresh water yield and the purity of the fresh water from a horizontal tubular solar seawater still (HTSSS) are higher than that from a BSSS under the same condition.…”
Section: Introductionmentioning
confidence: 99%